2019
DOI: 10.1002/psc.3164
|View full text |Cite
|
Sign up to set email alerts
|

Light waveguiding in bioinspired peptide nanostructures

Abstract: Basic optical properties of bioinspired peptide nanostructures are deeply modified by thermally mediated refolding of peptide secondary structure from α-helical to βsheet. This conformational transition is followed by the appearance in the β-sheet structures of a wideband optical absorption and fluorescence in the visible region.We demonstrate that a new biophotonic effect of optical waveguiding recently observed in peptide/protein nanoensembles is a structure-sensitive bimodal phenomenon. In the primary α-hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The generated light can be routed into waveguiding systems, allowing for functionalization and implementation of various detection strategies inside a PICs architecture. Waveguiding strategies in biophotonic systems can be divided into active, usually realized by means of fluorescence inside the waveguide material, excited by an external light source, and passive waveguiding, which can be realized in various ways, e.g., using air-clad, biocompatible spider silk [46] or peptide nanostructures (which could be used either as active or passive waveguides, depending on the fabrication steps taken) [47].…”
Section: Detectorsmentioning
confidence: 99%
“…The generated light can be routed into waveguiding systems, allowing for functionalization and implementation of various detection strategies inside a PICs architecture. Waveguiding strategies in biophotonic systems can be divided into active, usually realized by means of fluorescence inside the waveguide material, excited by an external light source, and passive waveguiding, which can be realized in various ways, e.g., using air-clad, biocompatible spider silk [46] or peptide nanostructures (which could be used either as active or passive waveguides, depending on the fabrication steps taken) [47].…”
Section: Detectorsmentioning
confidence: 99%
“…The natural abundance of biomaterials and biological entities has long served as a source of inspiration for designing tracers/devices as well as photonic structures that are capable of manipulating incident light [29]. Biological cells, microorganisms, and their derivatives, encompassing DNA, proteins, silk, biomaterials, and polysaccharides, exhibit diverse interactions with light, facilitating their use as photonics components like waveguides, micro lenses, lasers, and even gratings [30][31][32][33][34][35][36]. These innate biological materials and biological beings possess immense potential for innovating novel photonics tracers/devices tailored for biological imaging, detection, and restorative uses [20].…”
Section: Introductionmentioning
confidence: 99%
“…5 Interestingly, independently of their natural or synthetic origin, amyloid-like peptides generally emit fluorescence with a maximum in the blue field upon excitation with near-UV radiation (B370 nm). [6][7][8][9][10][11][12][13][14] Although the physicochemical determinants of these spectroscopic properties remain quite elusive, it has been recently shown that these assemblies can also emit in the red and near-infrared region when excited with radiation with wavelengths in the range 600-670 nm. 15 In this scenario, we have recently found that the human protein Pbx-regulating protein-1 (PREP1) [16][17][18] contains two cytotoxic amyloidogenic fragments, spanning residues 117-132 and 297-311.…”
mentioning
confidence: 99%
“…A remarkable number of studies have shown that these assemblies, independently of their natural or synthetic origin, frequently present some spectroscopic properties whose underlying physicochemical determinants remain still quite elusive. [6][7][8][9][10][11][12][13][14] In particular, they can emit a blue fluorescence upon excitation with near-UV radiation (B370 nm). Very recently, it has been shown that these assemblies are also able to emit at much higher wavelengths extending to the red and near-infrared region when excited with radiation with wavelengths in the range 600-670 nm.…”
mentioning
confidence: 99%